Pengaruh Gaya Kepemimpinan Paternalistik Dan Insentif Terhadap Kinerja Karyawan Melalui Motivasi Pada PT. Asco Dwi Mobilindo Surabaya - Alfito Yusuf Isa Sugihono; Safa’at Safa’at; Agung Dwi Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Human resources are a strategic asset that determines organizational success, making employee performance management essential. PT. Asco Dwi Mobilindo Surabaya has experienced an increase in absenteeism in 2024 and six employee resignations during 2022–2024, reflecting a decline in motivation and performance. This study aims to analyze the influence of paternalistic leadership style and incentives on employee performance with motivation as a mediating variable. The research employed a quantitative method with 35 employees selected through convenience sampling and analyzed using path analysis with SPSS 25. The results indicate that paternalistic leadership and incentives do not have a significant direct effect on employee performance but positively and significantly influence motivation. Furthermore, motivation has a positive and significant effect on employee performance and mediates the relationship between paternalistic leadership, incentives, and employee performance